Peran Pendidikan Al-Qur'an dalam Pembentukan Akhlak Siswa pada Pendidikan Dasar: Kajian Teoretis dan Praktis - Irfan; Muslimin; Aminullah; Nurlaila (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The role of Qur'anic education is crucial in the moral development of students, especially at the elementary education level. Through a value-based approach to the Qur'an, this education aims to shape students' character and morality, enabling them to exhibit good ethics in daily life. This study aims to analyze the role of Qur'anic education in the formation of students' character at the elementary level, using both theoretical and practical approaches. The study reviews the literature on the concept of Qur'anic education, its influence on students' character, and the implementation of Qur'anic learning in elementary schools. The results of the study indicate that when applied with appropriate methods, Qur'anic education can significantly influence the development of students' moral character, rooted in Islamic values of ethics and morality. Therefore, Qur'anic education in elementary schools plays a strategic role in shaping a generation with noble character.